Faktor-faktor yang Mempengaruhi Kepuasan Pengguna Kartu Telkomsel (Studi Kasus Pelanggan Kartu Telkomsel Batam) - Santi Irawati Sitohang; Triana Ananda Rustam (J-MAS (Jurnal Manajemen dan Sains), 2022)
There are problems that are quite important in the Telkomsel company, namely experiencing a decrease in customers, there are various causes for customers to experience a decline such as the form of service quality, prices, promotions. The purpose of this study was to see the effect of the influence of service quality, price and promotion either partially or simultaneously on customer satisfaction. Sources of data in this study are primary data, data collection method using google form, research data analysis using SPSS 25 assistance program. The tests carried out are classical assumption test, multiple linear regression and hypothesis testing with t test and f test. The sampling method used in this study was a purposive sampling method with a total of 204 people. The results of the study partially show that the conclusion is that the quality of service affects the satisfaction of Telkomsel card users, the price affects the satisfaction of Telkomsel card users, and promotions affect the satisfaction of Telkomsel card users. simultaneously Service quality, price and promotion affect the satisfaction of Telkomsel card users.